2016
DOI: 10.1111/head.12941
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Inadequate Response to Acute Migraine Medication: Results From the American Migraine Prevalence and Prevention (AMPP) Study

Abstract: These results provide a snapshot of the effectiveness of usual acute treatment as well as predictors of inadequate acute treatment response in a large population sample of people with episodic migraine. These results highlight the high rates of unmet treatment needs in people with migraine. Similarities and differences in predictors vary with outcome for reasons that are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
96
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(108 citation statements)
references
References 32 publications
7
96
1
Order By: Relevance
“…Cutaneous allodynia has been associated with an increased risk of attack recurrence and migraine chronicity . Cutaneous allodynia also predicts inadequate 2‐hour pain‐free and 24‐hour pain relief outcomes . Diagnostic vigilance remains important, and all consulting patients, especially women, should be queried about the presence of allodynia.…”
Section: Discussionmentioning
confidence: 99%
“…Cutaneous allodynia has been associated with an increased risk of attack recurrence and migraine chronicity . Cutaneous allodynia also predicts inadequate 2‐hour pain‐free and 24‐hour pain relief outcomes . Diagnostic vigilance remains important, and all consulting patients, especially women, should be queried about the presence of allodynia.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of migraine, a recent study showed that comorbid depression worsens the responsiveness for acute migraine treatment in a large population sample with episodic migraine (57). Thus, understanding the neurobiological background of this exceptionally high and specific comorbidity between migraine and depression may improve our treatment strategies.…”
Section: Discussionmentioning
confidence: 99%
“…In this study of persons with migraine, triptan users had favorable outcomes in comparison with the NSAID, opioid, and barbiturate treatment groups for the 2hPF and 24hPR outcome measures. In addition, the presence of allodynia significantly increased the likelihood of an inadequate response to treatment for the 2hPF and the 24hPR outcome measures, but not – as in our prior analysis where medications groups were combined – for the 24hSPR outcome. These results are consistent with some human treatment studies as well as laboratory research .…”
Section: Discussionmentioning
confidence: 59%
“…In addition, the presence of allodynia significantly increased the likelihood of an inadequate response to treatment for the 2hPF and the 24hPR outcome measures, but not – as in our prior analysis where medications groups were combined – for the 24hSPR outcome. These results are consistent with some human treatment studies as well as laboratory research . In addition to allodynia, significant predictors of inadequate response to acute treatment included higher pain intensity (triptans, NSAIDs, opioids) and greater monthly headache‐day frequency (triptans, NSAIDs, opioids, and ergot alkaloids).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation